Análisis del tipo de noticias presentadas y su respectiva comparación en los noticieros estelares de los medios de comunicación televisivos: Ecuavisa, Teleamazonas y TC Televisión de cobertura nacional. Período de investigación: septiembre, 2023. - Campoverde Vivanco, María José (2024)
Television is one of the main mass media worldwide. Its importance is given by its veracity regarding the informative content it broadcasts, which makes its credibility widely accepted by the public opinion. However, since its beginning, communication studies have focused on the influence of the media and the message on the opinion and perception that audiences have about reality. This research work focused on a comparative analysis of how information content is presented in three stellar news programs in Ecuador: Televistazo, 24 Horas and El Noticiero. For this purpose, an exploratory study was carried out with a mixed methodology. The number of news presented in the analyzed media was quantified, then the news was segmented according to its subject matter. With this scheme, the percentage of news generated in each of the topics was determined. Finally, an observation form was used to compare the approach that each media gives to the news that deal with the same topic. An average of 100 to 250 news items per week were studied and compared among the three newscasts, of which the highest percentage were of a social, political, police and entertainment nature. It was possible to highlight the scarce presence of news with cultural and scientific topics. The treatment of the news identified in the same subject matter is variable, as it adapts to the deontological codes of each media. In essence, what changes is the discourse of the presenters, the images they present since some news programs are inclined to be cruder and more yellowish in their informative content.